Precursor material and preparation method thereof, positive electrode material, secondary battery and electric device
By using the hexagonal nanosheet structure and spherical structure of nickel-manganese precursor material, the sintering temperature is reduced, and the problems of Li+ loss and oxygen defects of spinel nickel-manganese lithium manganese during high-temperature heat treatment are solved, and the capacity, circulation performance and volumetric energy density of the battery are improved.
Patent Information
- Application Number
- CN202411999357.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-11
AI Technical Summary
Li+ loss and oxygen defects are prone to occur during high-temperature heat treatment, resulting in local lithium deficiency, heterophase generation and reduced battery capacity.
A nickel-manganese precursor material is provided, with primary particles having a hexagonal nanosheet structure and secondary particles having a spherical shape. During sintering, the sintering temperature can be greatly reduced, thereby reducing Li+ loss, Mn3+ generation and Li/Ni mixed displacement.
By reducing the sintering temperature and reducing the heterogeneous phase generation, the battery capacity, circulation performance and volumetric energy density are improved.
Smart Images

Figure CN119797449A_ABST
Abstract
Description
Technical Field
[0001] The embodiments of the present application relate to precursor materials and preparation methods thereof, positive electrode materials, secondary batteries and electrical devices. Background Art
[0002] Spinel nickel lithium manganese oxide (LiNi 0.5 Mn 1.5 O4) because of its higher reaction potential (>4.7V, vs Li / Li + (represents the voltage value of the half-cell made with Li / Li+ as the negative electrode)), as well as a high theoretical specific capacity (>140mAh / g), low cost, and is used in high energy density power battery systems. However, pure phase, stoichiometric LiNi 0.5 Mn 1.5 O4 synthesis is difficult, and the following two problems are inevitable during high-temperature heat treatment:
[0003] 1)Li + The loss of lithium leads to local lithium deficiency and the formation of nickel impurities, such as Li x Ni 1-x O impurities;
[0004] 2) Oxygen deficiency, which leads to partial Mn 3+ The production of Mn 3+ Prone to disproportionation reaction to generate Mn 2+ and Mn 4+ , where Mn 2 + It is easy to generate Mn element, resulting in Mn in lithium nickel manganese oxide. 3+ A large amount of loss leads to a decrease in battery capacity.
[0005] Therefore, how to solve the above problems to improve the performance of lithium nickel manganese oxide is an issue that needs to be addressed urgently. Summary of the invention
[0006] The present invention provides a nickel-manganese precursor material, the primary particles of which are in a hexagonal nanosheet structure and the secondary particles are in a spherical shape. The sintering temperature can be greatly reduced during sintering, thereby reducing the loss of Li+ and Mn 3+ The generation of Li / Ni mixed arrangement can improve the battery capacity and cycle performance. At the same time, the positive electrode material sintered from the nickel-manganese binary precursor material has a spherical morphology, which can increase the compaction density and thus increase the volume energy density of the battery.
[0007] The present application provides a precursor material, the chemical formula of which is Ni x Mn y Me z(OH)2, wherein x+y+z=1, 0.20<x<0.40, 0.5<y<1, and 0≤z≤0.2, Me is a doping element, optionally, the doping element is selected from one or more of Mg, Al, Sr, Zr, W, Y, Ti, Co, and Me is 0-2000ppm, and the precursor material includes a secondary particle structure composed of primary particles; the primary particles include primary particles in a hexagonal nanosheet structure, the hexagonal side length of the hexagonal nanosheet structure is between 30nm-300nm, and the standard deviation of the hexagonal side length of the same hexagonal nanosheet structure is between 0-40nm. In the present application, if more than 80% of the primary particles on the surface of the precursor material are laid on the surface of the secondary particles, it is considered that the primary particles are laid on the surface of the secondary particles. The specific test method is: select at least 3 positions in the SEM image of each precursor material at a magnification of 50K, each position is an area of about 10μm by 10μm, and select at least 10 primary particles in each area to observe their morphology and whether they are laid on the surface of the secondary particles. If at least 80% of the primary particles on the surface of the precursor material are laid on the surface of the secondary particles, it is considered that the primary particles on the surface of the precursor material are laid on the surface of the secondary particles. Furthermore, the ratio of the side length (L) of the hexagonal nanosheet structure to the thickness (H) of the hexagonal nanosheet structure is 2-7 (in the same field of view).
[0008] In some embodiments, the thickness of the hexagonal nanosheet structure is between 10 nm and 100 nm, and optionally, between 30 nm and 80 nm.
[0009] Furthermore, the secondary particles of the precursor material are spherical. In some embodiments, the surface of the secondary particles is a spherical surface, wherein 3μm<Dv50<10μm, and 0.80<distance<1.20, distance=(Dv90-Dv10) / Dv50, wherein Dv50 represents the particle size of the secondary particles from the small particle size side to 50% of the volume accumulation in the volume-based particle size distribution, Dv90 represents the particle size of the secondary particles from the small particle size side to 90% of the volume accumulation in the volume-based particle size distribution, and Dv10 represents the particle size of the secondary particles from the small particle size side to 10% of the volume accumulation in the volume-based particle size distribution. Specifically, when the diameter distance is too small, the number of hexagonal nanosheet structures generated is small and the sintering temperature reduction is limited; when the diameter distance is too large, the secondary particles will seriously agglomerate after sintering. Therefore, when 0.80<diameter distance<1.20, the sintering temperature can be lowered while the hexagonal nanosheet structure is formed, and the secondary particles will not agglomerate after sintering.
[0010] Other embodiments of the present application provide a method for preparing a precursor material, comprising: mixing raw materials including nickel salts and manganese salts to obtain a mixed solution, and performing a coprecipitation reaction; when the particle size Dv50 of the product reaches 75%-85% of the target particle size, the pH value of the material is increased by 0.5-2.0 within 0.5h-3h, wherein Dv50 represents the particle size of the secondary particles starting from the small particle size side and reaching 50% of the volume accumulation in the volume-based particle size distribution; and when the particle size Dv50 of the material reaches the target particle size, the material is collected to obtain the precursor material. In some embodiments, the method increases the pH value of the material by 0.5-2.0 within 0.5h-1h. In some embodiments, the target particle size is in the range of 3μm-10μm.
[0011] The present application also provides a positive electrode material, which is obtained by sintering the above-mentioned precursor material at a temperature of 800-1000°C.
[0012] In summary, the primary particles of the nickel-manganese binary precursor material provided in this application are in a hexagonal nanosheet structure, and the secondary particles are in a spherical shape. The sintering temperature can be greatly reduced during sintering, thereby reducing Li + Loss, Mn 3+ The formation of Li / Ni mixed arrangement, etc., thereby improving the battery capacity and cycle performance. At the same time, the positive electrode material sintered from the nickel-manganese binary precursor material has a spherical morphology, which can increase the compaction density and thus increase the volume energy density of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0013]
[0013] The corresponding aspects of the embodiments of the present disclosure are best understood from the following detailed description when read in conjunction with the accompanying drawings.
[0014] Figure 1A A scanning electron microscope image of primary particles of the nickel-manganese precursor material of Example 1 is shown.
[0015] Figure 1B A scanning electron microscope image of secondary particles of the nickel-manganese precursor material of Example 1 is shown.
[0016] Figure 1C A scanning electron microscope image of the positive electrode material after sintering the corresponding nickel-manganese precursor material of Example 1 is shown.
[0017] Figure 1C-1 The XRD pattern of the positive electrode material of Example 1 is shown.
[0018] Figure 1D A scanning electron microscope image of the positive electrode material after sintering the corresponding nickel-manganese precursor material of Example 2 is shown.
[0019] Figure 1D-1 The XRD pattern of the positive electrode material of Example 2 is shown.
[0020] Figure 2A A scanning electron microscope image of primary particles of the nickel-manganese precursor material of Comparative Example 1 is shown.
[0021] Figure 2B A scanning electron microscope image of the secondary particles of the nickel-manganese precursor material of Comparative Example 1 is shown.
[0022] Figure 2C A scanning electron microscope image of the positive electrode material after sintering the corresponding nickel-manganese precursor material of Comparative Example 1 is shown.
[0023] Figure 2C-1 The XRD pattern of the positive electrode material of Comparative Example 1 is shown.
[0024] Figure 2D A scanning electron microscope image of the positive electrode material after sintering the corresponding nickel-manganese precursor material of Comparative Example 2 is shown.
[0025] Figure 2D-1 The XRD pattern of the positive electrode material of Comparative Example 2 is shown. DETAILED DESCRIPTION
[0026] Research has found that spinel lithium nickel manganese oxide (LiNi 0.5 Mn 1.5 The sintered morphology of lithium ion battery (O4) (i.e., the morphology of the corresponding positive electrode material) has a classic octahedral and chamfered polyhedral structure, among which the (111) face will undergo serious rearrangement when the electrolyte is infiltrated, which will lead to increased lattice strain, causing the (111) face to crack easily, and will cause Jahn-Teller distortion and accelerate surface corrosion; the (001) face can avoid serious Mn dissolution due to the appropriate distribution of Mn and Li atoms; the Mn atoms on the (110) face are arranged loosely and have an open structure, which is conducive to the transmission of Li+. In addition, the chamfered polyhedral structure has a higher sphericity, which is conducive to higher volume energy density and good processing performance. Therefore, more and more researchers are studying and developing spinel lithium manganese oxide materials with chamfered polyhedral structures. After the precursor is sintered, in order to obtain spinel lithium manganese oxide materials with chamfered polyhedral structures, the sintering temperature is generally increased to above 900°C, or even above 1000°C. However, higher sintering temperatures inevitably cause Li+ loss and oxygen defects, leading to loss of electrochemical performance. However, the precursor material provided in this application further avoids the above problems caused by excessively high sintering temperatures. In other words, by using the nickel-manganese binary precursor material provided in this application, the sintering temperature can be reduced, the generation of impurities can be reduced, and the battery capacity, cycle performance, and volume energy density can be improved.
[0027] Specifically, the present application provides a precursor material, the chemical formula of which is Ni x Mny Me z (OH)2, wherein x+y=z=1, 0.20<x<0.40, 0.5<y<1, and 0≤z≤0.2, Me is a doping element, optionally, the doping element is selected from one or more of Mg, Al, Sr, Zr, W, Y, Ti, Co, and optionally Me is 0-2000ppm, the precursor material comprises a secondary particle structure composed of primary particles; the primary particles comprise primary particles in a hexagonal nanosheet structure, the hexagonal side length of the hexagonal nanosheet structure is between 30nm-300nm, and the standard deviation of the hexagonal side length of the same hexagonal nanosheet structure is between 0-40nm; and the primary particles located on the surface of the precursor material are laid flat on the surface of the secondary particles, in some embodiments, the ratio of the side length (L) of the hexagonal nanosheet structure to the thickness (H) of the hexagonal nanosheet structure is 2-7 (under the same field of view), wherein: under a scanning electron microscope (SEM) at 50K, regardless of whether it is the same secondary particle, the following conditions are met:
[0028] ① The upper limit of the ratio of the hexagonal side length L of the hexagonal nanosheet structure / the thickness H of the hexagonal nanosheet structure = the maximum side length a1 of the hexagonal nanosheet structure / the minimum thickness b1 of the hexagonal nanosheet structure (for all the hexagonal nanosheet structures in the SEM image, a1 and b1 are not the same hexagonal nanosheet structure);
[0029] ② The lower limit of the ratio of the hexagonal side length L of the hexagonal nanosheet structure / the thickness H of the hexagonal nanosheet structure = the minimum side length a2 of the hexagonal nanosheet structure / the maximum thickness b2 of the hexagonal nanosheet structure (for all the hexagonal nanosheet structures in the SEM image, a2 and b2 are not the same nanosheet).
[0030] Further, in the present application, the primary particles located on the surface of the precursor material are spread on the surface of the secondary particles. In the present application, if more than 80% of the primary particles located on the surface of the precursor material are spread on the surface of the secondary particles, it is considered that the primary particles are spread on the surface of the secondary particles. The specific test method is: select at least 3 positions in the SEM image of each precursor material at a magnification of 50K, each position is an area of about 10μm by 10μm, and select at least 10 primary particles in each area to observe their morphology and whether they are spread on the surface of the secondary particles. If at least 80% of the primary particles located on the surface of the precursor material are spread on the surface of the secondary particles, it is considered that the primary particles located on the surface of the precursor material are spread on the surface of the secondary particles. In some embodiments, less than 20% of the primary particles located on the surface of the precursor material can be inserted obliquely on the surface of the secondary particles.
[0031] In some embodiments, the thickness of the hexagonal nanosheet structure is between 10 nm and 100 nm, and optionally, between 30 nm and 80 nm.
[0032] Furthermore, the secondary particles of the precursor material are spherical. In some embodiments, the surface of the secondary particles is a spherical surface, wherein 3μm<Dv50<10μm, and 0.80<distance<1.20, distance=(Dv90-Dv10) / Dv50, wherein Dv50 represents the particle size of the secondary particles from the small particle size side to 50% of the volume accumulation in the volume-based particle size distribution, Dv90 represents the particle size of the secondary particles from the small particle size side to 90% of the volume accumulation in the volume-based particle size distribution, and Dv10 represents the particle size of the secondary particles from the small particle size side to 10% of the volume accumulation in the volume-based particle size distribution. Specifically, when the diameter distance is too small, the number of hexagonal nanosheet structures generated is small and the sintering temperature reduction is limited; when the diameter distance is too large, the secondary particles will seriously agglomerate after sintering. Therefore, when 0.80<diameter distance<1.20, the sintering temperature can be lowered while the hexagonal nanosheet structure is formed, and the secondary particles will not agglomerate after sintering.
[0033] In summary, the primary particles of the nickel-manganese binary precursor material provided in this application are in a hexagonal nanosheet structure, and the secondary particles are in a spherical shape. The sintering temperature can be greatly reduced during sintering, thereby reducing Li + Loss, Mn 3+ The formation of Li / Ni mixed arrangement, etc., thereby improving the battery capacity and cycle performance. At the same time, the positive electrode material sintered from the nickel-manganese binary precursor material has a spherical morphology, which can increase the compaction density and thus increase the volume energy density of the battery.
[0034] In addition, the synthesis method of the present application adopts the coprecipitation method which is more common in the industry for synthesis, and there is no need to add an inducing agent, etc. The process is simple and easy to industrialize. Specifically, the method for preparing the above-mentioned precursor material provided by the present application includes: mixing raw materials including nickel salts and manganese salts to obtain a mixed solution, and conducting a coprecipitation reaction; when the particle size Dv50 of the product reaches 75%-85% of the target particle size, the pH value of the material is increased by 0.5-2.0 within 0.5h-3h, wherein Dv50 represents the particle size of the secondary particles starting from the small particle size side and reaching 50% of the volume accumulation in the volume-based particle size distribution; and when the particle size Dv50 of the material reaches the target particle size, the material is collected to obtain the precursor material. Furthermore, the method for preparing the precursor material provided by the present application uses nickel salts, manganese salts, doping salts (optionally), precipitants, and complexing agents as raw materials. The synthesis method is as follows:
[0035] 1) Mixed salt preparation: Prepare a mixed solution of nickel salt, manganese salt and / or doping salt (optional).
[0036] 2) Material synthesis I: Add the prepared mixed solution, precipitant and complexing agent to the reactor. Control the pH value (8.0-11.0) and ammonia value (2g / L-8g / L) to react, and test the particle size Dv50 of the material in the reactor in real time;
[0037] 3) Material synthesis II: When the particle size Dv50 of the material in the kettle reaches 75%-85% of the target particle size (3μm-10μm), the pH value in the kettle is increased to (0.5-2.0) within (0.5-3.0, optionally 0.5-1) h and then the synthesis is continued. When the particle size Dv50 of the material in the kettle reaches the target particle size, the material is collected.
[0038] 4) Material processing: solid-liquid separation, washing, drying, etc. of the collected material to obtain a nickel-manganese precursor material with a special morphology of a hexagonal nanosheet structure. In some embodiments, the precipitant includes but is not limited to sodium hydroxide (NaOH) and potassium hydroxide (KOH); the complexing agent includes but is not limited to ammonia water.
[0039] The present application also provides a positive electrode material, which is obtained by sintering the above-mentioned precursor material at a temperature of 800-1000°C.
[0040] In addition, some other embodiments of the present application provide a secondary battery and a corresponding electrical device, wherein the secondary battery includes a positive electrode plate, wherein the positive electrode plate includes the above-mentioned positive electrode material. Further, the preparation process of the secondary battery is as follows:
[0041] (1) Preparation of positive electrode materials
[0042] ① Add the mixed solution of nickel salt, manganese salt and / or doping salt, NaOH solution and ammonia solution into the reactor containing the base liquid at a set rate through a metering pump at the same time. The base liquid includes an alkaline solution containing ammonium ions, wherein the ammonium ion concentration is (2-8) g / L, and the pH value of the base liquid is (8.0-11.0). The reactor temperature is (40-60) ° C, the stirring speed is (400-600) rpm, the flow rate of the mixed solution is controlled at (2.0-4.0) L / h, the synthetic ammonia value is controlled at (2-8) g / L, and the pH value is controlled at (8.0-11.0), and the particle size growth in the reactor is carried out.
[0043] ② When the particle size Dv50 of the material in the kettle reaches 75%-85% of the target particle size (3μm-10μm), the pH value in the kettle is controlled online to increase by (0.5-2.0) within (0.5-3.0) h, and the particle size growth in the kettle continues until the particle size in the reactor reaches the target particle size, stop feeding, and obtain a precursor slurry.
[0044] ③ The precursor slurry is transported to a centrifuge for solid-liquid separation and washing, and then dried, sieved, demagnetized and packaged to obtain the nickel-manganese precursor material Ni x Mn y Me z (OH)2, wherein x+y=z=1, 0.20<x<0.40, 0.5<y<1, and 0≤z≤0.2, Me is a doping element (one or more of Mg, Al, Sr, Zr, W, Y, Ti, Co), optionally, Me is 0-2000ppm. The secondary particles of the precursor material are spherical, 3μm<Dv50<10μm, 0.80<diameter distance<1.20; the primary particles are hexagonal nanosheet structures, the side length of the hexagonal nanosheet structure is (30-300)nm, the thickness of the hexagonal nanosheet structure is (10-100)nm, at least 80% of the primary particles of the hexagonal nanosheet structure are flat on the spherical surface and less than 20% of the primary particles are obliquely inserted on the spherical surface.
[0045] ④ The nickel-manganese precursor material, lithium salt and optional Me1 compound (Me1 is one or more of the doping elements Mg, Al, Sr, Zr, W, Y, Ti, Co, optionally, Me1 is 0-2000ppm) are mixed to obtain a mixed material. The mixed material is sintered: the sintering atmosphere is air, the gas pressure is (5-25) Pa, the sintering temperature is (800-1000) ° C, and the heat preservation is (8-20) h to obtain the positive electrode material.
[0046] (2) Preparation of positive electrode sheet
[0047] The prepared positive electrode material, conductive agent, and binder are mixed in a suitable amount of NMP (N-methylpyrrolidone) solvent to form a conductive glue according to the mass ratio commonly used in the art (such as a mass ratio of 90:5:5), and then the positive electrode material is added to the conductive glue in proportion, and a homogenizer is used to mix evenly to form a positive electrode slurry, and the positive electrode slurry is applied to the positive electrode collector to form a positive electrode material layer, thereby obtaining a positive electrode sheet. In some embodiments, the positive electrode collector is, for example, a foil formed by surface treatment of nickel, titanium, aluminum, silver, stainless steel or carbon. In addition to the foil, the positive electrode collector can also be used in any one or more combinations of various forms such as film, mesh, porous, foam, etc. Among them, the thickness of the positive electrode collector is, for example, 8μm to 15μm. In this embodiment, the positive electrode collector is, for example, aluminum foil, and the thickness of the aluminum foil is, for example, 13μm. The positive electrode current collector has two oppositely disposed surfaces along its own thickness direction, and the positive electrode material layer can be disposed on the surface on either side thereof, or on both surfaces.
[0048] As an example, the positive electrode binder is selected from any one or more of polyvinylidene fluoride (PVDF), polyethylene oxide (PEO), polyamide (PA), polyacrylonitrile (PAN), polyacrylate, polyvinylether, polymethyl methacrylate (PMMA), ethylene-propylene-diene terpolymer (EPDM), polyhexafluoropropylene or styrene butadiene rubber (SBR). The positive electrode conductive agent is selected from one or at least two of conductive carbon black (Super P), acetylene black, graphene, carbon nanotubes, carbon nanofibers, etc. The ratio of the positive electrode material, the conductive agent and the binder in the positive electrode material layer can be set according to the conventional settings in the art.
[0049] (3) Preparation of negative electrode sheet
[0050] The negative electrode material, negative electrode conductive agent, binder and thickener are dispersed in a solvent to form a uniform negative electrode slurry, and the negative electrode slurry is coated on the surface of the negative electrode current collector. After drying, cold pressing and other processes, a negative electrode material layer is formed on the negative electrode current collector to obtain a negative electrode sheet. The ratio between the components in the negative electrode slurry can be set with reference to the conventional ratio, and is not limited here. In some embodiments, the negative electrode material is the negative electrode material on the negative electrode current collector as conventionally understood in the art. The type of negative electrode material can be carbon material, silicon material, lithium metal or "composite material of carbon material and silicon material", and the carbon material can be natural graphite, artificial graphite, soft carbon, hard carbon, etc.; silicon material such as elemental silicon, silicon oxide compound, silicon carbon compound, etc. The negative electrode conductive agent is selected from one of carbon black, acetylene black, graphene, carbon nanotubes, carbon nanofibers, etc., or a combination of two or more mixed in any proportion. The negative electrode binder is selected from one or a combination of sodium carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), polyacrylic acid, lithium polyacrylate, fluororubber, and PVDF; the thickener can be sodium carboxymethyl cellulose (CMC-Na).
[0051] (4) Preparation of electrolyte
[0052] The electrolyte infiltrates the positive electrode sheet and the negative electrode sheet. During the battery charging and discharging process, lithium ions are inserted and removed back and forth between the positive electrode sheet and the negative electrode sheet, and the electrolyte plays a role in conducting lithium ions. The electrolyte can be selected from conventional combinations in the art.
[0053] In one embodiment, the electrolyte includes an organic solvent and a lithium salt, wherein the organic solvent may be selected from one or more of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), etc. The lithium salt may be selected from one of LiPF6 (lithium hexafluorophosphate), LiBF4 (lithium tetrafluoroborate), LiClO4 (lithium perchlorate), LiAsF6 (lithium hexafluoroarsenate), LiFSI (lithium bis(trifluoromethanesulfonyl)imide), LiTFSI (lithium bis(trifluoromethanesulfonyl)imide), LiTFS (lithium trifluoromethanesulfonate), LiDFOB (lithium difluorooxalatoborate), LiBOB (lithium dioxalatoborate), LiPO2F2 (lithium difluorophosphate), LiDFOP (lithium difluorobis(oxalatophosphate), LiTFOP (lithium tetrafluorooxalatophosphate), or a combination thereof in any proportion. The molar concentration of lithium salt in the electrolyte is 0.5 mol / L to 2 mol / L. In other embodiments, some film-forming additives and functional additives that can improve battery performance may be added to the electrolyte, for example, vinylene carbonate (VC), 1,3-propane sultone (PS), dithiothreitol (DTD), etc., and those skilled in the art may select them according to actual needs.
[0054] (5) Preparation of diaphragm
[0055] In some embodiments, the separator is disposed between the positive electrode plate and the negative electrode plate to play an isolating role. The separator may be, for example, a polyethylene film (PE), a polypropylene film (PP), a glass fiber film, a polyethylene film or a composite film. The thickness of the separator is 9 to 18 μm, the air permeability is 180 s / 100 mL to 380 s / 100 mL, and the porosity is 30% to 50%.
[0056] (6) Preparation of secondary batteries
[0057] The positive electrode sheet, the separator and the negative electrode sheet are sequentially placed into the mold for assembly; after assembly, the electrolyte is injected, and after formation and packaging, the secondary battery of the lithium manganese battery is obtained.
[0058] Those skilled in the art will understand that the above-described method for preparing the battery is only an example, and other methods commonly used in the art may be used without departing from the contents disclosed in the present application.
[0059] The reagents and raw materials used in the present invention are commercially available.
[0060] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples.
[0061] Example 1
[0062] (1) Preparation of positive electrode materials
[0063] Precursor material preparation
[0064] ① Add MnSO4·H2O and NiSO4·6H2O to the stirred deionized (DI) water to form a mixed solution, and add the mixed solution, NaOH solution and ammonia solution to the reactor containing the bottom liquid at a set rate through a metering pump at the same time. The bottom liquid includes an alkaline solution containing ammonium radicals, wherein the ammonium radical concentration is 7g / L and the pH value of the bottom liquid is 9. The reactor temperature is 50°C, the stirring speed is 500rpm, the flow rate of the mixed solution is controlled at 3L / h, the synthetic ammonia value is controlled at 7g / L, and the pH value is controlled at 9, and the particle size growth in the reactor is carried out.
[0065] ② When the particle size Dv50 of the material in the kettle reaches 75%-85% of the target particle size (7μm-10μm), the pH value in the kettle is controlled online to increase by 2.0 within 1h, that is, the pH is increased to 11, and the particle size growth in the kettle continues until the particle size in the reactor reaches the target particle size, stop feeding, and obtain a precursor slurry.
[0066] ③ The precursor slurry is transported to a centrifuge for solid-liquid separation and washing, and then dried, sieved, demagnetized and packaged to obtain the nickel-manganese precursor material Ni 0.25 Mn 0.75 (OH)2. In this embodiment, the secondary particles of the precursor material are spherical, 7μm<Dv50<10μm, 0.80<diameter distance<1.20; the primary particles are hexagonal nanosheet structures, the side length of the hexagonal nanosheet structure is (80-140)nm, the standard deviation of the hexagonal side length is between 0-40nm, the thickness of the hexagonal nanosheet structure is (25-40)nm, at least 80% of the primary particles of the hexagonal nanosheet structure are flat on the spherical surface and less than 20% of the primary particles are obliquely inserted on the spherical surface.
[0067] Cathode material preparation
[0068] ④ The nickel-manganese precursor material and lithium salt are mixed to obtain a mixed material. The mixed material is sintered: the sintering atmosphere is air, the gas pressure is 15 Pa, the sintering temperature is 910° C., and the heat preservation is carried out for 10 hours to obtain the positive electrode material.
[0069] Further, Figure 1A The scanning electron microscope image of the primary particles of the nickel-manganese precursor material of Example 1 is shown, Figure 1B shows a scanning electron microscope image of the secondary particles of the nickel-manganese precursor material of Example 1, and Figure 1C A scanning electron microscope image of the positive electrode material after sintering the corresponding nickel-manganese precursor material of Example 1 is shown.
[0070] Example 2
[0071] The preparation method is consistent with that of Example 1, except that in step ④ of Example 2, the sintering temperature used to prepare the positive electrode material is 850°C.
[0072] Since the nickel-manganese precursor material in Example 2 is the same as that in Example 1, the scanning electron microscope images of the primary particles and the secondary particles of the nickel-manganese precursor material in Example 2 are as follows: Figure 1A and Figure 1B As shown, however, the SEM image of the positive electrode material of Example 2 is as shown Figure 1D shown.
[0073] Example 3
[0074] The preparation method is consistent with that of Example 1, except that in step ④ of Example 3, the sintering temperature used to prepare the positive electrode material is 800°C.
[0075] Example 4
[0076] The preparation method is consistent with that of Example 1, except that in step ④ of Example 4, the sintering temperature used to prepare the positive electrode material is 1000° C., thereby obtaining the positive electrode material.
[0077] Example 5
[0078] The preparation method is consistent with that of Example 1, except that in Example 5: the precursor material is doped with doping elements Al and Zr. Specifically, in step ①, Al salt (Al2(SO4)3·18H2O) and Zr salt (Zr(SO4)2·4H2O) are added to stirred deionized (DI) water to form a precursor material doped with Al and Zr. The Al and Zr contents in the prepared precursor material are each 1000ppm; the sintering temperature used to prepare the positive electrode material is then adjusted to 850°C, thereby forming a positive electrode material doped with Al and Zr.
[0079] Example 6
[0080] The preparation method is consistent with that of Example 1, except that in Example 6:
[0081] The pH value in the online control kettle is increased by 1.0 within 3 hours, that is, the pH is increased to 10, and the particle size growth in the kettle is continued until the particle size in the reactor reaches the target particle size, and the feeding is stopped to obtain a precursor slurry. In this embodiment, the primary particles are in a hexagonal nanosheet structure, the side length of the hexagonal nanosheet structure is (220-300) nm, the standard deviation of the hexagonal side length is between 0-40 nm, the thickness of the hexagonal nanosheet structure is (70-100) nm, at least 80% of the primary particles of the hexagonal nanosheet structure are flat on the spherical surface and less than 20% of the primary particles are obliquely inserted on the spherical surface.
[0082] Afterwards, the sintering temperature used in preparing the positive electrode material was 890°C.
[0083] Example 7
[0084] The preparation method is consistent with that of Example 1, except that in Example 7:
[0085] The pH value in the online control kettle is increased by 0.5 within 0.5h, that is, the pH is increased to 9.5, and the particle size growth in the kettle is continued until the particle size in the reactor reaches the target particle size, and the feeding is stopped to obtain a precursor slurry. In this embodiment, the primary particles are in a hexagonal nanosheet structure, the side length of the hexagonal nanosheet structure is (150-250) nm, the standard deviation of the hexagonal side length is between 0-40nm, the thickness of the hexagonal nanosheet structure is (40-65) nm, at least 80% of the primary particles of the hexagonal nanosheet structure are flat on the spherical surface and less than 20% of the primary particles are obliquely inserted on the spherical surface.
[0086] Afterwards, the sintering temperature used in preparing the positive electrode material was 860°C.
[0087] Example 8
[0088] The preparation method is consistent with that of Example 1, except that in Example 8:
[0089] The pH value in the online control reactor is increased by 2 within 0.5h, that is, the pH is increased to 11, and the particle size growth in the reactor is continued until the particle size in the reactor reaches the target particle size, and the feeding is stopped to obtain a precursor slurry. In this embodiment, the primary particles are in a hexagonal nanosheet structure, the side length of the hexagonal nanosheet structure is (30-70) nm, the standard deviation of the hexagonal side length is between 0-40nm, the thickness of the hexagonal nanosheet structure is (10-15) nm, at least 80% of the primary particles of the hexagonal nanosheet structure are flat on the spherical surface and less than 20% of the primary particles are obliquely inserted on the spherical surface.
[0090] Afterwards, the sintering temperature used in preparing the positive electrode material was 820°C.
[0091] Example 9
[0092] The preparation method is consistent with that of Example 1, except that in Example 9:
[0093] The base liquid includes an alkaline solution containing ammonium radicals, wherein the ammonium radical concentration is 2 g / L, and the pH value of the base liquid is 11. The temperature of the reactor is 40°C, the stirring speed is 600 rpm, the flow rate of the mixed solution is controlled at 2.0 L / h, the synthetic ammonia value is controlled at 2 g / L, and the pH value is controlled at 11, and the particle size growth in the reactor is carried out, and the secondary particles of the precursor material are spherical, 3 μm<Dv50<5 μm.
[0094] Afterwards, the sintering temperature used in preparing the positive electrode material was 850°C.
[0095] Example 10
[0096] The preparation method is consistent with that of Example 1, except that in Example 10:
[0097] The base liquid includes an alkaline solution containing ammonium radicals, wherein the ammonium radical concentration is 8 g / L, and the pH value of the base liquid is 8. The temperature of the reactor is 60°C, the stirring speed is 400 rpm, the flow rate of the mixed solution is controlled at 4.0 L / h, the synthetic ammonia value is controlled at 8 g / L, and the pH value is controlled at 8, and the particle size growth in the reactor is carried out, and the secondary particles of the precursor material are spherical, 4 μm<Dv50<7 μm.
[0098] Afterwards, the sintering temperature used in preparing the positive electrode material was 850°C.
[0099] Comparative Example 1
[0100] The preparation method is consistent with that of Example 1, except that in Comparative Example 1:
[0101] The step ② of preparing the positive electrode material is not included, that is, there is no step of increasing the pH, and the sintering temperature used in preparing the positive electrode material is the same as that in Example 1. Further, Figure 2A The scanning electron microscope image of the primary particles of the nickel-manganese precursor material of Comparative Example 1 is shown, Figure 2B The scanning electron microscope image of the secondary particles of the nickel-manganese precursor material of Comparative Example 1 is shown, and Figure 2C A scanning electron microscope image of the positive electrode material after sintering the corresponding nickel-manganese precursor material of Comparative Example 1 is shown.
[0102] Comparative Example 2
[0103] The preparation method is consistent with that in Example 1, except that in Comparative Example 2:
[0104] The step ② of preparing the positive electrode material is not included, that is, there is no step of increasing the pH. In addition, the sintering temperature used in preparing the positive electrode material is 850° C., thereby obtaining the positive electrode material.
[0105] Since the nickel-manganese precursor material in Comparative Example 2 is the same as that in Comparative Example 1, the scanning electron microscope images of the primary particles and the secondary particles of the nickel-manganese precursor material in Comparative Example 2 are as follows: Figure 2A and Figure 2B As shown, however, the scanning electron microscope image of the positive electrode material of Comparative Example 2 is as shown Figure 2D shown.
[0106] The positive electrode materials prepared in the above-mentioned Examples 1-2 and Comparative Examples 1-2 were subjected to XRD test (scanning angle 10° to 80°, step length 0.02°, dwell time 0.6S), and the test results were as follows: Figure 1C-1 , Figure 1D-1 , Figure 2C-1 as well as Figure 2D-1 As shown. Figure 1C-1 It can be seen that the positive electrode material prepared in Example 1 has no obvious Li x Ni 1-x The diffraction peaks of the impurity phase of the rock salt were not found in the positive electrode material prepared in Example 2 at 2θ = 37°, 43°, and 64°. x Ni 1-x The positive electrode material prepared in Comparative Example 1 has obvious diffraction peaks of LixNi1-xO rock salt impurity phase at 2θ=37° and 64°, and the positive electrode material prepared in Comparative Example 2 has no obvious diffraction peaks of LixNi1-xO rock salt impurity phase at 2θ=37°, 43°, and 64°. x Ni 1-x O diffraction peak of rock salt impurity phase. Comparing Example 1-1 with Comparative Example 1, at the same sintering temperature, the positive electrode material prepared in Example 1-1 is spherical and the primary particles are larger; comparing Example 1-2 with Comparative Example 1, it can be seen that the positive electrode material prepared in Example 1-2 of the present application can form chamfered octahedrons at a lower sintering temperature and can reduce the generation of impurity phases. Comparing Example 1-2 with Comparative Example 2, it can be seen that when Comparative Example 2 is sintered at the same temperature, the positive electrode material is an agglomerated octahedron and the octahedron is less developed, which is not conducive to the formation of chamfered octahedrons.
[0107] The positive electrode materials in the above-mentioned Examples 1-10 and Comparative Examples 1-2 can be formed into secondary batteries by the following method.
[0108] For example, the positive electrode sheet: the prepared nickel manganese spinel positive electrode material, conductive agent, and binder are mixed in a mass ratio of 90:5:5, and the conductive agent and binder are first added to an appropriate amount of NMP (N-methylpyrrolidone) solvent to form a conductive glue, and then the positive electrode material is added to the conductive glue in proportion, and mixed evenly with a homogenizer and then coated to form a positive electrode sheet. In the above embodiment, the conductive agent is selected from carbon black. The positive electrode binder is selected from PVDF. Negative electrode sheet: The negative electrode active material silicon carbon material and graphite, the negative electrode conductive agent acetylene black, the binder styrene butadiene rubber latex and the thickener sodium carboxymethyl cellulose (CMC) are mixed in a mass ratio of 89:8:1:1:1, dispersed in a solvent (deionized water), stirred under the action of a vacuum mixer to form a uniform negative electrode slurry, and the negative electrode slurry is coated on the surface of the negative electrode collector (8μm copper foil). After drying, cold pressing and other processes, a negative electrode active material layer is formed on the negative electrode collector to obtain a negative electrode sheet. Electrolyte: The organic solvent in the electrolyte is a mixed solution containing ethylene carbonate (abbreviated as EC), ethyl methyl carbonate (abbreviated as EMC) and diethyl carbonate (abbreviated as DEC), wherein the weight ratio of EC, EMC and DEC is 1:1:1. The electrolyte is LiPF6, and the total content of LiPF6 is 12.5% of the total weight of the electrolyte. Diaphragm: A porous PE membrane with a thickness of 11um is used as the diaphragm (wherein the thickness of the diaphragm is 9μm to 18μm; the air permeability is 180s / 100mL to 380s / 100mL; the porosity is 30% to 50%). Finally, the positive electrode sheet, the diaphragm and the negative electrode sheet are sequentially placed into the mold for assembly; after assembly, the electrolyte is injected, and after formation and packaging, the secondary battery of the lithium manganese battery is obtained.
[0109] In addition, in the present application, the positive electrode materials in the above examples 1-10 and comparative examples 1-2 were prepared into button cells for testing, as follows:
[0110] Positive electrode sheet: The positive electrode materials in the above examples 1-10 and comparative examples 1-2 are used as the main positive electrode materials, and conductive carbon black (Super P) and polyvinylidene fluoride (PVDF) are also included. The mass ratio of the positive electrode material to these substances is 90:5:5. The method for preparing the positive electrode sheet includes the following steps: firstly, the positive electrode material, Super P, and PVDF are mixed in the above proportions, and then nitrogen methyl pyrrolidone (NMP) is gradually added with high-speed stirring to prepare a positive electrode slurry with a certain viscosity. Then the prepared slurry is evenly coated on aluminum foil, placed in a blast drying oven and dried at 120°C for 10 minutes, and finally the dried electrode sheet is rolled, cut, and made into a positive electrode sheet. Negative electrode sheet: A metal lithium foil is used as the negative electrode. The diaphragm is 8μm to 14μm; the air permeability is 150s / 100mL to 350s / 100mL; the porosity is 30% to 50%. The electrolyte is lithium salt LiPF6, with a content of 4-24wt%. The mass ratio of EC, EMC, DMC and PC in the solvent is (2 to 4):(3 to 5):(2 to 4):(0 to 1), and when the mass ratio is (2 to 4):(3 to 5):(2 to 4):0, it means that the solvent does not contain PC. The prepared positive electrode sheet and the metal lithium negative electrode sheet are assembled into a CR2032 button half-cell commonly used in this field.
[0111] Then the charge and discharge capacity and cycle performance of the above button battery were tested, as follows:
[0112] First, the button-type half-cell battery was activated by charging and discharging at 0.1C at 25°C within the battery operating voltage range of 3.50V (discharge cut-off voltage) to 4.95V (charge cut-off voltage). Then, the battery was tested.
[0113] (1) Initial charge / discharge capacity test: After the prepared positive electrode material is assembled and charged, a charge and discharge test is performed at 0.33C / 0.33C between 3.50 and 4.95V.
[0114] (2) 100cls cycle performance test: After the prepared positive electrode material is assembled and charged, it is cycled at 0.33C / 1C for 100 cycles between 3.50 and 4.95V to examine the material's cycle capacity retention rate, specifically, the 100-cycle capacity retention rate (100-cycle capacity retention rate = discharge specific capacity after 100 cycles / initial discharge specific capacity*100%).
[0115] (3) Compaction density test: Weigh 2 g of the prepared positive electrode material and use a Yuanneng compaction density meter to perform a compaction density test in the “2-probe” mode.
[0116] (4) Test of the length, thickness and standard deviation of primary particles: Select at least 3 positions in the SEM image of each precursor material at a magnification of 50K, each position is an area of about 10 μm by 10 μm, and select at least 10 primary particles in each area. Use nano measure software to measure the length and thickness of each primary particle; remove the first and last data, and take the length and thickness data of 80% of the middle section as the length and thickness data of the primary particles, and then calculate the length standard deviation.
[0117] The test results of the above-mentioned Examples 1-10 and Comparative Examples 1-2 are shown in Table 1 below.
[0118] Table 1. Test results of cathode material performance of Examples 1-10 and Comparative Examples 1-2
[0119]
[0120]
[0121] It can be seen from the above examples 1-8 that the precursor material Ni provided in this application x Mn y Me z (OH)2, wherein x+y=z=1, 0.20<x<0.40, 0.5<y<1, and 0≤z≤0.2, Me is a doping element, optionally, the doping element is selected from one or more of Mg, Al, Sr, Zr, W, Y, Ti, Co, and further, Me is 0-2000ppm, wherein the primary particles of the precursor material are in a hexagonal nanosheet structure, the hexagonal side length of the hexagonal nanosheet structure is between 30nm-300nm, optionally between 80nm-140nm, the standard deviation of the hexagonal side length is between 0-40nm, and the ratio of the side length (L) of the hexagonal nanosheet structure to the thickness (H) of the hexagonal nanosheet structure is 2-7. It can be seen from Examples 1-4 that the above-mentioned precursor material can be sintered within the sintering temperature range of (800-1000)℃, and the sintering temperature can be greatly reduced during sintering, thereby reducing Li + Loss, Mn 3+ It can be seen that the primary particles of the nickel-manganese binary precursor material provided by the present application are in a hexagonal nanosheet structure, and the secondary particles are in a spherical shape. The sintering temperature can be greatly reduced during sintering, thereby reducing Li + Loss, Mn 3+The generation of Li / Ni mixing, etc., thereby improving the battery capacity and cycle performance. At the same time, the positive electrode material sintered from this nickel-manganese binary precursor material has a spherical morphology, which can improve the compaction density and thus improve the volume energy density of the battery. In addition, it can be seen from Examples 1, 6-8 that when the pH value in the online control kettle is increased by (0.5-2.0) within (0.5-3.0) h, the precursor material with a hexagonal nanosheet structure of the primary particles of the present application can be obtained, which can affect the length and thickness of the hexagonal side of the hexagonal nanosheet structure of the primary particles.
[0122] Furthermore, it can be seen from Examples 1-4 that the positive electrode material can be formed at a relatively low sintering temperature (800-1000° C.) using the precursor material provided by the present application. Figures 1A to 1D and FIG. 2A to FIG. 2D Comparing Examples 1-2 and Comparative Examples 1-2, it can be seen that when the precursor material in Example 1 is sintered at a temperature of 910°C, the secondary particles are spherical in shape, the chamfered structure is more obvious, and the positive electrode material particles formed are larger. At a sintering temperature of 850°C in Example 2, the positive electrode material formed has an octahedral structure, and the positive electrode material particles that can be formed at a lower temperature (850°C) are smaller and have good dispersibility. It can be seen that in the present application, the chamfered structure of the precursor material formed at a lower sintering temperature is similar to a spherical morphology, which can increase the compaction density of the positive electrode material and increase the volume energy density. The positive electrode material particles formed in Comparative Example 1 have obvious sharp corners (the chamfered structure is not obvious) and the compaction density is poor. In Comparative Example 2, the positive electrode material formed at 850°C is an agglomerated octahedral structure with poor dispersibility, and the secondary particles formed cannot grow. Therefore, the precursor material provided in the present application can reduce the sintering temperature, reduce the generation of impurities, and improve the battery capacity, cycle performance, and volume energy density.
[0123] The features of several embodiments are summarized above so that those skilled in the art can better understand aspects of the present invention. Those skilled in the art should understand that they can easily use the present invention as a basis to design or modify other processes and structures for implementing the same purpose and / or achieving the same advantages as the embodiments introduced herein. Those skilled in the art should also appreciate that this equivalent construction does not deviate from the spirit and scope of the present invention, and that they can make multiple changes, substitutions and changes herein without departing from the spirit and scope of the present invention.
Claims
1. A precursor material, characterized in that: The chemical formula is Ni x Mn y Me z (OH)2, wherein x+y=z=1, 0.20<x<0.40, 0.5<y<1, and 0≤z≤0.2, Me is a doping element; The precursor material includes a secondary particle structure composed of primary particles; The primary particles include primary particles in a hexagonal nanosheet structure, the hexagonal side length of the hexagonal nanosheet structure is between 30nm and 300nm, and the standard deviation of the hexagonal side length of the same hexagonal nanosheet structure is between 0nm and 40nm; and The primary particles located on the surface of the precursor material are laid flat on the surface of the secondary particles.
2. The precursor material according to claim 1, characterized in that The ratio of the side length of the hexagonal nanosheet structure to the thickness of the hexagonal nanosheet structure is 2-7.
3. The precursor material according to claim 1, characterized in that The hexagonal side length of the hexagonal nanosheet structure is between 80nm and 140nm; and / or, The thickness of the hexagonal nanosheet structure is between 10nm and 100nm; and / or, The thickness of the hexagonal nanosheet structure is between 30nm and 80nm.
4. The precursor material according to claim 1, characterized in that The secondary particles of the precursor material are spherical in structure, wherein 3 μm<Dv50<10 μm, and 0.80<diameter distance<1.20, wherein the diameter distance=(Dv90-Dv10) / Dv50, Here, Dv50 represents the particle size of the secondary particles reaching 50% of the volume accumulation from the small particle size side in the volume-based particle size distribution. Dv90 represents the particle size of the secondary particles reaching 90% of the volume accumulation from the small particle size side in the volume-based particle size distribution, and Dv10 represents the particle size at which the volume accumulation of the secondary particles reaches 10% from the smaller particle size side in the volume-based particle size distribution.
5. The precursor material according to claim 1, characterized in that The doping element is selected from one or more of Mg, Al, Sr, Zr, W, Y, Ti, and Co.
6. A method for preparing a precursor material according to any one of claims 1 to 5, characterized in that: include: Mixing raw materials including nickel salt and manganese salt to obtain a mixed solution, and performing a coprecipitation reaction; When the particle size Dv50 of the product reaches 75%-85% of the target particle size, the pH value of the material is increased by 0.5-2.0 within 0.5h-3h, wherein Dv50 represents the particle size of the secondary particles from the small particle size side to 50% of the volume accumulation in the volume-based particle size distribution; and When the particle size Dv50 of the material reaches the target particle size, the material is collected to obtain the precursor material.
7. The method according to claim 6, characterized in that Increase the pH value of the material by 0.5-2.0 within 0.5h-1h.
8. A positive electrode material, characterized in that The precursor material is obtained by sintering the precursor material according to any one of claims 1 to 5 at a temperature of 800-1000°C.
9. A secondary battery, characterized in that: include: A positive electrode sheet, comprising the positive electrode material according to claim 8.
10. An electrical device, characterized in that: The secondary battery according to claim 9 is included.
Citation Information
Patent Citations
Nickel cobalt lithium manganite precursor of nanosheet agglomeration secondary particle and preparing method thereof
CN106745336A
Positive electrode material precursor and preparation method thereof, positive electrode material and lithium ion battery
CN109994726A
Hexagonal flaky lithium nickel cobalt manganate oxide precursor and preparation method thereof
CN111293305A
Positive electrode material precursor for sodium ion battery and preparation method of positive electrode material precursor
CN117800410A